Spatial uniformity of the spectral radiance by white LED-based K2CaP2O7:Ce3+, Tb3+ phosphor - Ha Thanh Tung; My Hanh Nguyen Thi (Bulletin of Electrical Engineering and Informatics, 2023)
The K2CaP2O7:Ce3+, Tb3+ (Ce/Tb-KCPO) phosphor with blue-to-green emission is introduced in this study. The synthesis of the phosphor is carried out with the solid-state approach. The phosphor characteristics, including X-ray diffraction, luminescence lifespan, and thermal stability are measured and examined. The data show that Ce/Tb-KCPO phosphor displays a broadband emission from blue to green when excited by ultraviolet source. Besides, the ion Ce3+ strengthen the emission of Tb3+ ion through an efficient energy-transfer mechanism, which is estimated about 82.51%. The main electric interaction responsible for this Ce/Tb energy transfer is the dipole-quadrupole one. The phosphor also benefits the luminous intensity and color uniformity of the light-emitting diodes (LED) white-light output. Therefore, the Ce/Tb-KCPO phosphor can be a potential material for high-power white light-emitting diodes (WLED).